Molecular and Phylogenetic Study of Sarcocystis Gigantia from Different Slaughterhouse Regions in Karbala province - Kawther A.M. Al-Mussawi 1, Hayder A. Muhammed 2 , Saja A. M. Al-Saadi 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sarcocystis diseases caused a serious illness in sheep flock which inducing decrease of growth conversion rates and complete or partial loss of carcasses at the abattoirs, This article which described an prevalence of parasites Sarcocystis gigantea in sheep slaughtered in a farm in kerbala governerate, Iraq, and performed a phylogenetic analysis by using the Euclidean distances calculation from the Sarcosystis gigntea nucleotide frequencies around the world sarcosystis genomes. Fifty sheep showed multiple nodules in the esophagus that were microscopically characterized as encapsulated cysts filled with elongated, nucleated structures morphologically consistent with S. gigantea bradyzoites. The preverlance and species of Sarcocystis gigantia were revealed as 10% (5 out f 50) for the macroscopic sarcosystis , the shape of these cysts were resembled to oval and pear shape, the sensitivity of Polymerase chain reaction was 75% with 95% of confidence intervals 19.41% to 99.37% and the specificity was 95.65% with 95% of confidence intervals 85.16% to 99.47%. Our results suggest that oligonucleotide sequences were useful for estimation of Sarcocystis gigntea phylogenetic relationships for closely related species.